Digital media, sharing, and everyday life - Kennedy, Jenny (Postdoctoral researcher) ([Place of publication not identified] ROUTLEDGE, 2018)
Digital Media, Sharing and Everyday Life provides nuanced accounts of the processes of sharing in digital culture and the complexities that arise in them. The book explores definitions of sharing, and the roles that our digital devices and the platforms we use play in these practices. Drawing upon practice theory to outline a theoretical framework of sharing practice, the book emphasizes the need for a coherent and consistent framework of sharing in digital culture and explains what this framework might look like. With insightful descriptions, the book draws out the relationship of sharing to privacy and control, the labored strategies and boundaries of reciprocation, and our relationships with the technologies which mediate sharing practices. The volume is an essential read for researchers, postgraduate and undergraduate students in Media and Communication, New Media, Sociology, Internet Studies, and Cultural Studies.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Media Studies; COMPUTERS / Social Aspects / General; SOCIAL SCIENCE / Sociology / General; Digital media -- Social aspects; Digital communications -- Social aspects; Information society; Sharing; Privacy, Right of